2011
DOI: 10.1007/s12237-011-9377-7
|View full text |Cite
|
Sign up to set email alerts
|

The Growth of Estuarine Resources (Zostera marina, Mercenaria mercenaria, Crassostrea virginica, Argopecten irradians, Cyprinodon variegatus) in Response to Nutrient Loading and Enhanced Suspension Feeding by Adult Shellfish

Abstract: While many coastal ecosystems previously supported high densities of seagrass and abundant bivalves, the impacts of overfishing, eutrophication, harmful algal blooms, and habitat loss have collectively contributed to the decline of these important resources. Despite improvements in wastewater treatment in some watersheds and subsequent reduced nutrient loading to neighboring estuaries, seagrass and bivalve populations in these locations have generally not recovered. We performed three mesocosm experiments to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 90 publications
1
23
0
Order By: Relevance
“…Kroncke et al (1998) believe that climate variability may have a larger effect on benthic ecosystems than eutrophication and some other possible factors, but Paerl (2006) suggests it has been difficult to distinguish between these two effects. Nitrogen enrichment does lead to increases in shell growth and soft tissues in quahogs, softshell clams, and bay scallops (Carmichael et al, 2004;Wall et al, 2011Wall et al, , 2013. Anoxia can occur when phytoplankton blooms die in eutrophic waters, killing larvae and postset bivalves.…”
Section: Human Factorsmentioning
confidence: 99%
“…Kroncke et al (1998) believe that climate variability may have a larger effect on benthic ecosystems than eutrophication and some other possible factors, but Paerl (2006) suggests it has been difficult to distinguish between these two effects. Nitrogen enrichment does lead to increases in shell growth and soft tissues in quahogs, softshell clams, and bay scallops (Carmichael et al, 2004;Wall et al, 2011Wall et al, , 2013. Anoxia can occur when phytoplankton blooms die in eutrophic waters, killing larvae and postset bivalves.…”
Section: Human Factorsmentioning
confidence: 99%
“…Several studies have concentrated on the seeding breeding, cultivation, and growth performance of M. mercenaria (Weiss et al, 2002;Zhang et al, 2003;Chung et al, 2007;Weiss et al, 2007;Zarnoch and Schreibman, 2008;Arnold et al, 2009;Wall et al, 2011Wall et al, , 2013, but only a few have investigated its physiological ecology (Sma and Baggaley, 1976;Grizzle et al, 2001;Wen et al, 2004;Parent et al, 2008). In addition, suspension-feeding bivalves are well known for their active biodeposition capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Many models have tried to explain the relationship between the light attenuation coefficient and water quality , Dennison et al 1993, Wall et al 2011. Dennison et al (1993) found the minimum water quality characteristics using water column chlorophyll a (15 μg/L), total suspended solids (15 mg/L), dissolved inorganic nitrogen (DIN) (10 μM) and dissolved inorganic phosphorous (DIP) (0.67 μM) to sustain submerged aquatic vegetation (SAV) in the Chesapeake Bay and its tributaries.…”
Section: Sediment Characteristicsmentioning
confidence: 99%
“…Many studies use plant productivity as a way to quantify photosynthetic stress (Peterson and Heck 2001, Carroll et al 2008, Wall et al 2011, Skinner et al 2013). Peterson and Heck (2001) used productivity to quantify positive interactions between Thalassia testudinum and bivalves and found that the presence of mussels at densities greater than 500 m -2 reduced epiphytic loads on leaves and resulted in increased productivity.…”
Section: Stress Measurementsmentioning
confidence: 99%